Analisis Self-branding: Persepsi Mahasiswa Universitas Tidar terhadap Prabowo Subianto - Maulana, Tiorizal; Mawarni, Aruming Sekar; Salsabila, Reva Isyana; Kirani, Dinda Adia; Khasanah, Putri Nur; Nugraha, Joko Tri (FIA Unkris Press, 2025)
This study aims to analyze the understanding of Tidar University students regarding the self-branding strategy employed by Prabowo Subianto as a prominent national political figure. Self-branding is defined as a conscious and deliberate process of shaping a strong personal image through various communication channels, both direct and mediated via digital platforms. The study adopts a quantitative approach using a survey method, with a closed-ended questionnaire distributed randomly to 100 student respondents. The instrument is constructed based on four key indicators of self-branding: verbal communication, visual representation, social media usage, and the portrayal of leadership qualities. The collected data were analyzed using descriptive and inferential statistical techniques through SPSS software. The findings reveal that the majority of respondents perceived Prabowo’s self-branding efforts positively, particularly in terms of his assertive speech style that reflects a strong and charismatic personality. However, perceptions of his digital media image consistency varied among students, suggesting challenges in maintaining coherent messaging across platforms. Overall, the study concludes that Prabowo's self-branding strategy is effective in creating a robust public image among the student demographic. These findings contribute to the broader discourse in political communication studies, particularly regarding how public figures shape and maintain their personal brand in a rapidly evolving digital information landscape where perceptions can shift quickly due to media influence and social discourse.